The Efficacy and Safety of Intranasal Formulations of Ketamine and Esketamine for the Treatment of Major Depressive Disorder: A Systematic Review - Ludivine Boudieu; Myriam Mennetrier; Pierre-Michel Llorca; Ludovic Samalin (Pharmaceutics, 2023)
Ketamine and its enantiomers represent an innovative glutamatergic agent as a treatment for individuals with treatment-resistant depression (TRD) and major depressive disorder (MDD) with suicidal ideation and behavior. Intranasal (IN) formulations could allow for quick onset of action on depressive symptoms as well as a reduction in side effects by bypassing the blood–brain barrier compared with administration via the intravenous route. The aim of this review was to provide an up-to-date analysis of the data on the efficacy and safety of IN ketamine and IN esketamine for the treatment of MDD. A systematic review following PRISMA guidelines was conducted. Databases (PubMed, Embase, MEDLINE, PsycINFO, and Google Scholar) were searched to capture articles about IN ketamine or IN esketamine for MDD. This systematic review highlighted the interest in IN routes of ketamine and esketamine for MDD patients with TRD or active suicidal ideation. They provide a rapid onset of antidepressant action within the first hours after administration. Nevertheless, the evidence of efficacy is stronger for IN esketamine than for IN ketamine in MDD patients. The safety profile appears to be acceptable for IN esketamine but requires further studies, and a more accurate IN delivery device is required for ketamine.